National Newborn Screening Tests Carried Out with Heel Lance and Their Importance - Sibel İçke; Rabia Ekti Genç (Galenos Yayinevi, 2017)
Inbreeding is very common in our country, and this brings along various congenital metabolic diseases. In order to detect the congenital metabolic diseases at an early stage, lots of screening tests are carried out on the newborn. In Turkey, the metabolic diseases which are in the scope of newborn screening program are phenylketonuria, congenital hypothyroidis, biotinidase deficiency, and cystic fibrosis. The screening test is carried out with the blood sample obtained by heel lance. The aim of the screening tests is to identify the babies with diseases, and start treatment as soon as possible in order to prevent irrevocable damage.